Agency in the darkness: 'fear of the unknown', learning disability and teacher education for inclusion. Issue 4 (3rd April 2018) - Robinson, Deborah; Goodey, Chris
ABSTRACT: This paper proposes inclusion phobia as a sharper and more operative definition of the 'fear of the unknown' often cited as an explanation for resistance to inclusive education. Using 'severe and profound learning disability' as the paradigm case, we situate the phobia surrounding this label in its social and historical context. Our hypothesis is that resistance to inclusion for this group is not rational but amounts to a thought disorder in a psychiatric sense. Using qualitative case studies of pre-service teachers on practicum and headteachers engaged in decisions about admissions, we demonstrate the workings and impact of inclusion phobia. We illustrate its trajectory from a general social dysfunction, to the systems that channel it to the individuals caught up in it. Our aim is to expose inclusion phobia so that, teacher educators, teachers and pre-service teachers might, in knowing it, find new ways to remedy it. In doing so, long standing resistance to inclusive education is made more tractable. We conclude with our own proposals for an anti-phobic curriculum for teacher education.